Antioxidant and antibacterial activity of sappan wood (Caesalpinia sappan L.) kombucha - Zubaidah, Elok; Salafy, Rahma Aulia; Ningtyas, Dian Widya; Denty Wiryawan, Alivianisa Carissa (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2024)
Sappan wood (Caesalpinia sappan Linn) is well known for its antioxidants, anti-inflammatories, and antibacterials. Unfortunately, this plant has not been used properly. In this study, sappan wood is processed into a kombucha drink through fermentation. Kombucha fermentation gives sappan wood drink a distinct and pleasant flavor while improving quality. The study aimed to increase the functional value of kombucha using sappan wood as raw material. Kombucha was prepared with sappan wood powder (16 mesh size) at various concentrations (0.4, 0.8, 1.2, 1.6, and 2% (w/v)) and 10% (w/v) sugar concentration. The effect of various sappan wood concentrations as a substrate for kombucha demonstrated a significant (p<0.05) reduction in pH and improvement in total phenol content, IC50 value of antioxidant activity, and antibacterial activity against E. coli. The best sappan wood kombucha treatment was obtained at a concentration of 1.2% with pH of 3.85, total phenol of 874.44 mg GAE/mL, total sugar of 6.62%, IC50 value of 85.43 ppm, antibacterial activity against E. coli of 8.57 mm, and antibacterial activity against S. aureus of 7.99 mm.